2019
DOI: 10.4103/jpi.jpi_29_18
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Prognostic Factors in the Digital Era: Comparison of Nottingham Grade using Whole Slide Images and Glass Slides

Abstract: Background: To assess reproducibility and accuracy of overall Nottingham grade and component scores using digital whole slide images (WSIs) compared to glass slides. Methods: Two hundred and eight pathologists were randomized to independently interpret 1 of 4 breast biopsy sets using either glass slides or digital WSI. Each set included 5 or 6 invasive carcinomas (22 total invasive cases). Participants interpreted the same biopsy set approximately 9 months later followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
10
2
Order By: Relevance
“…Although we have demonstrated that interobserver agreement for Nottingham grade using LM is not inferior to that reported using WSI in a previous study, a tendency towards a lower mitotic count in WSI was observed 18,19 …”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Although we have demonstrated that interobserver agreement for Nottingham grade using LM is not inferior to that reported using WSI in a previous study, a tendency towards a lower mitotic count in WSI was observed 18,19 …”
Section: Discussioncontrasting
confidence: 64%
“…16,17 Although we have demonstrated that interobserver agreement for Nottingham grade using LM is not inferior to that reported using WSI in a previous study, a tendency towards a lower mitotic count in WSI was observed. 18,19 The guidelines and diagnostic criteria for mitoses that are well established and currently in use are derived from LM practice, and whether they can be applied as such to WSIs or need further adjustments remains to be investigated before using WSI in routine practice. The lack of defined criteria for assessing mitoses digitally may lead to inconsistent reporting, which would have clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most studies, especially the most recent publications, overall diagnostic concordance was above the cutoff of 95% recommended in the CAP guidelines for WSI vali-dation, and discordances with a potential impact on clinical management were often lower than 3% ( 8 , 10 , 21 , 29 – 31 ). Another frequently reported area of discordance, as well source of dissatisfaction among pathologists, when using WSI relates to counting mitoses, such as is required in grading meningiomas ( 32 ) or breast carcinoma ( 33 , 34 ) or when diagnosing malignancy in a melanocytic lesion ( 35 ). Other less frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies in dysplasia assessment and grading can have 2 broad contributory factors. Davidson et al 33 observed a 27% intraobserver disagreement using glass slides in assigning a Nottingham grade to cases of invasive breast carcinoma. Similar figures have long been obtained in studies examining intraobserver agreement in grading of cervical intraepithelial neoplasia 34 and Gleason grading of prostatic acinar adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%